Salary standardization ([Quezon City] GMA Radio Television News and Public Affairs)
Discusses SSL and its effects on government employees and public school teachers. The discussants are from the Department of Budget and Management, Sec. Guillermo Carague, Carol Almeda from COURAGE and Eric Torres from the Alliance of Concerned Teachers (ACT).
VHS.
Host, Jose Mari Velez.
Keywords: Philippines -- Government employees -- Salaries, etc